O problema da moralidade na estética de Schiller - LINDOSO, Matheus Bahia (2026)
Schiller's aesthetics constitute a fundamental path toward addressing the moral problems of modern man. By discussing issues related to art, politics, and the very exploration of the impulses that are part of human nature, the playwright and philosopher Schiller opens up space for us to consider the contributions aesthetics makes to the customs and character of individuals. Although the categories of art and morality are often thought of as distinct elements, these two particularities share a certain connection in Schiller's thought, as the artistic, in its own way, influences a form of reflection and contribution to the ethical, political, and cultural problems faced by humankind in the Age of Enlightenment. With this understanding in mind, this research focuses on morality as a central point in Schiller's aesthetic reflections, seeking to demonstrate how, through the phenomenon of art, art can play a morally formative role in individuals, enabling these moral subjects to act and express themselves freely within the cultural context in which they find themselves. Following a dual approach, this research seeks first to explore Schiller's youth and adulthood, demonstrating how the moral element permeates his thought, particularly in his works: “The Robbers”; “Kallias, or on Beauty”; and “The Aesthetic Education of Man”. Secondly, drawing on his “Naive and Sentimental Poetry” and several essays that comprise “Theory of Tragedy”, we will examine how the relationship between art and morality is debated and how the former can infuse the latter with a reflective direction for the betterment of human beings in society.